Buenas Prácticas Docentes Para Profesor De Inglés En El Ámbito Universitario - Merino, Daniela Fernanda Guano; Peñafiel, Marcelo Eduardo Allauca; Maribel, Salazar Silva Verónica (European Scientific Journal, ESJ, 2018)
The following investigation’s objective was to establish that virtual platforms are considered as didactic support for good teaching practices in English language teaching. The research is quasi-experimental of the transversal type that makes a bibliographic, statistical and descriptive analysis. It considered two groups control and experimental; which were represented by 94 students who entered the first level of the Language Center of the Escuela Superior Politecnica de Chimborazo. The members of each group were evaluated before and after developing the academic activities, through a set of activities established in an evaluation rubric, which were validated by academic experts in the English area. The experimental group used a virtual platform; while the experimental group applied the traditional processes (without virtual platform). Both groups developed the contents of a micro curricular plan with an evaluation rubric. Through the scientific and hypothetical method, the evaluations obtained in a partial and final manner were compared; determining that, the academic performance of the experimental group improved with respect to the traditional one, concluding that the use of the virtual platforms it is a good teaching practice for the teaching of the English language.